1989
DOI: 10.1007/bf00285294
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril does not alter renal function in normotensive, normoalbuminuric, hyperfiltering Type 1 (insulin-dependent) diabetic children

Abstract: Summary. Using a prospective randomised double-blind crossover design, the effect of the angiotensin converting enzyme inhibitor enalapril compared to a placebo was studied in 18 normotensive, normoalbuminuric Type 1 (insulin-dependent) diabetic children. Each patient had a high normal or dearly elevated glomerular filtration rate (145 ml.min -1. 1.73 m 2 or higher) in the 6 months prior to the study. Enalapril, 0.5 mg.kg -1. day -1, was given for 4 weeks followed by placebo for 4 weeks, or vice versa. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…GFR tended to decline, but no significant difference was noted between groups. In MA type 1 diabetes patients treated with ACE-is or a betablocker during 3-5 years, GFR was not affected [20,25,26,31], although some observed an initial fall in GFR during the first 6 months of treatment [31]. The previously observed increase in severity of morphological changes between 10 and 16 years' duration in our NA/NT patients with diabetes [15] was not confirmed during the 5-year observation period of this study.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…GFR tended to decline, but no significant difference was noted between groups. In MA type 1 diabetes patients treated with ACE-is or a betablocker during 3-5 years, GFR was not affected [20,25,26,31], although some observed an initial fall in GFR during the first 6 months of treatment [31]. The previously observed increase in severity of morphological changes between 10 and 16 years' duration in our NA/NT patients with diabetes [15] was not confirmed during the 5-year observation period of this study.…”
Section: Discussioncontrasting
confidence: 78%
“…Although candesartan had no apparent effect on UAE, most of our patients had very low UAE at baseline and follow-up; the majority had no measurable UAE. In MA and proteinuric patients with diabetes, however, several authors have reported significant decline in UAE after treatment with ARBs and ACE-is [8,16,17,24,[26][27][28][29][30]. GFR tended to decline, but no significant difference was noted between groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dear Sir, While accepting the suggestion from Drummond et al [1] that an increase in glomerular filtration rate (GFR) is secondary to a rise in renal plasma flow, I am unsure that any other conclusions can be drawn from this study especially with reference to intervention for the prevention of long-term diabetic nephropathy. My concern centres around the selection of the subjects.…”
Section: Enalaprii Therapy In Type 1 (Insulin-dependent) Diabetic Chimentioning
confidence: 84%
“…Despite their small patient populations, these studies have often been characterized by careful clinical phenotyping (GFR by clearance methods) and even kidney biopsy. In addition to the above-mentioned study of Cook and colleagues [9], an 8-week cross-over study by Drummond and coworkers [42] of enalapril versus placebo in 18 normotensive, normoalbuminuric children with T1DM showed that the ACEI reduced blood pressure but had no short-term effect on the GFR or AER compared to placebo. A two-biopsy study by Rudberg and colleagues [43] compared 13 adolescent and young adult patients (mean age 18.8 years) with T1DM and microalbuminuria treated with either enalapril or metoprolol and also compared the outcomes with those of nine untreated T1DM control patients.…”
Section: Studies In Children and Adolescentsmentioning
confidence: 94%